Research on the influence of thermal expansion of steel shaft on dynamic characteristics of full ceramic bearing-rotor system. (July 2022) - Guo, Jiancheng; Wu, Yuhou; Zhang, Xiaochen; Zhang, Yu; Wang, He; Bai, Xu; Lu, He
Bearing as the core components of high-grade CNC machine tools, with the constant change of internal clearance of bearing wear increasingly aggravated, spindle rotation accuracy reduced. In this paper, the idea of control variable method is used to explore the dynamic change of bearing clearance from different speeds and different radial loads. Starting with the dynamic model of bearing vibration, the theoretical model of rolling bearing with five degrees of freedom is established in this paper. The interaction force between steel shaft and ceramic bearing inner ring is calculated by Runge-Kutta method with elastic wall thickness ring theory, and the reduction of radial clearance of bearing is obtained. Therefore, a dynamic model of ceramic bearing considering the extrusion force of ceramic bearing inner ring is proposed. At the same time, the vibration test of steel shaft-all-ceramic bearing is designed and carried out. The test results show that under the same load, the higher the rotating speed, the shorter the time for the bearing-rotor system to reach temperature stability, and the root mean square of ceramic bearing-rotor system is obviously reduced. At the same speed, the greater the load, the more obvious the root mean square increase of the bearing-rotor system.